2017
DOI: 10.1128/jvi.00479-17
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus Pseudotyped with Ebola Virus Glycoprotein Serves as a Protective, Noninfectious Vaccine against Ebola Virus Challenge in Mice

Abstract: The recent Ebola virus (EBOV) epidemic in West Africa demonstrates the potential for a significant public health burden caused by filoviral infections. No vaccine or antiviral is currently FDA approved. To expand the vaccine options potentially available, we assessed protection conferred by an EBOV vaccine composed of vesicular stomatitis virus pseudovirions that lack native G glycoprotein (VSVΔG) and bear EBOV glycoprotein (GP). These pseudovirions mediate a single round of infection. Both single-dose and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 75 publications
(90 reference statements)
4
23
0
Order By: Relevance
“…Recent reports have shown that neutralization is not an absolute requirement for a MAb to protect in vivo against influenza and Ebola viruses ( 21 25 ). Specifically, murine IgG2a and IgG2b MAbs have exhibited protection in the mouse model driven by effector functions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have shown that neutralization is not an absolute requirement for a MAb to protect in vivo against influenza and Ebola viruses ( 21 25 ). Specifically, murine IgG2a and IgG2b MAbs have exhibited protection in the mouse model driven by effector functions.…”
Section: Resultsmentioning
confidence: 99%
“…More such antibodies could exist for Ebola virus, but may not have been pursued because initial antibody downselection is typically based on neutralization. In many EBOV vaccine studies, total antibody binding, rather than neutralization, is the best correlate of protection (Lennemann et al, 2017; Pushko et al, 2000; Schmaljohn and Lewis, 2016; Sullivan et al, 2009; Wong et al, 2012). Antibodies that recognize the IEF-linked, more accessible Tier 1 epitopes may even take precedence in polyclonal responses elicited by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…These B cells may therefore possess unappreciated antibody-independent roles such as priming T cells, and only produce antibodies with T cell help following vaccination, which promote but are not predictive of survival. Protection by a replication-deficient vaccine based on VSV pseudotyped with EBOV GP was mediated by GP-specific binding antibodies (IgG and IgM) and not neutralizing antibodies [36]. Collectively, these studies raised the issue that EBOV vaccine platforms elicit distinct immune profiles and use different protection mechanisms [37] thus emphasizing that individual studies are required for each proposed vaccine platform to establish vaccine-specific mechanistic correlate(s) of protection.…”
Section: Mechanistic Immune Correlates Of Protection: Distinct Contrimentioning
confidence: 99%